The Effect of Self-Efficacy and Career Planning on Career Decisions of Final Year Students with Family Support as a Moderating Variable - Sopacua, Yanes Heykel; Santoso, Budi; Handaru, Agung Wahyu (LPPPIPublishing, 2024)
The level of open unemployment in Jakarta for college graduates is still high. Students as instruments of education are expected to be able to compete and decide with certainty on their career choices after graduation. One aspect that must be prepared before graduation is their preparation and belief in their abilities. This study aims to analyze the effect of independent variables, namely Self-Efficacy and Career Planning with Family Support as a moderator on the dependent variable, namely Career Decisions of Final Year Students. This study uses the Structural Equation Modeling (SEM) method with Partial Least Square (PLS) analysis tools and uses SmartPLS 4.0 software. The population in this study were final year students of the Management study program, Faculty of Economics, State University of Jakarta. The results of this study indicate that (1) Self-efficacy has a positive and significant influence on the career decisions of final year students. (2) Career planning has a positive and significant influence on the career decisions of final year students. (3) Family support as a moderator has no effect on the relationship between self-efficacy and career planning on the career decisions of final year students.